Prevalence of seasonal affective disorder among primary health care attendees in eastern Riyadh-a cross-sectional study - Alqahtani, Mesfer Abdullah; Sayeed, Shibli; Marie, Mohammed Ali; Aedh Nasser, Bin Fardan; Meshal Bin Ali, Al Dileelan; Maeedh Faraj, Al Anazi; Basmah Dalli, Al Anazi; Munayfah Saadi, Al Mutairi; Ismail, Ismail Ahmad (International Journal Of Community Medicine And Public Health, 2023)
Background: Seasonal affective disorder (SAD), a type of mood disorder, is defined by seasonal depressive symptoms that appear at a particular time of a year. Its burden in Saudi Arabia is poorly understood. In this study, we aimed to estimate the prevalence of and factors associated with seasonal depression among attendees of primary health care centres (PHC) in Eastern Riyadh. Methods: We conducted a cross-sectional study in the PHC of Eastern Riyadh. We systematically sampled participants attending the PHCs the required sample size was achieved. We measured seasonal depression and beliefs using the validated seasonal pattern assessment questionnaire (SPAQ) and seasonal beliefs questionnaire. We presented the mean and standard deviation (SD) of scores obtained and used Student’s t test ANOVA test to compare differences across explanatory variables. We demonstrated internal consistency using Cronbach’s alpha. Results: Among 232 participants, majority were aged 18-35 years (67.2%) and males (60.8%). The mean (SD) score on SPAQ was 1.00 (0.71) and that on the seasonal beliefs was 3.03 (0.69). With a cut-off of 11 on SPAQ, prevalence of SAD was found to be 33.5%. SPAQ score was significantly higher among younger ages, females, single/divorced, Saudis, those with secondary/lower level education and those who earn<50,000 Saudi Riyals (p<0.001). Seasonal beliefs score was significantly higher among younger ages (p=0.013) and Saudis (p=0.001). Both the scales used had high internal consistency (Cronbach’s alpha of 0.901 for SPAQ and 0.847 for seasonal beliefs questionnaire). Conclusions: SAD was a prevalent mental health issue among primary care attendees in Eastern Riyadh. Screening for such conditions at the primary level among high-risk groups should be considered by family physicians.